Psychopathic Personality Traits and Empathy in Business and Psychology: An Examination of the Attraction, Selection and Attrition Cycle in Higher Education. - Litten, Verity Emma (Curtin University, 2019)
Attracting and selecting students that are well suited to their academic discipline is associated with improved student outcomes. This research is the first to test the utility of the Attraction, Selection and Attrition framework in higher education. Findings indicate that attraction, selection and socialisation processes contribute to increased personality homogenisation within business and psychology academic disciplines. These findings can be used to inform educational recruitment practices which subsequently determine the future of these professions.